Odpowiedzi

2009-11-26T00:22:38+01:00
Wiedząc że:
a) log₁₄2=a→→log₂14=1/a→→log₂2+log₂7=1/a→→log₂7=1/a -1=(1-a)/a→→
log₇2=a/(1-a)

log₁₄5=b→→ log₅14=1/b→→log₅2+log₅7=1/b

log₇5=1/log₅7=1/ {log₂7/log₂5}=log₂5/log₂7=log₂5 /(1-a)/a
log₅7=[(1-a)/a]:log₂5=[(1-a)/a]*log₅2
czyli:
log₅7=[(1-a)/a]*log₅2
log₅2+log₅7=1/b→→log₅2=1/b-log₅7

log₅7=[(1-a)/a]*[1/b-log₅7]
z tego powinno się obliczyć log₅7 ale czy się gdzieś nie rąbnełam, bo coś zawiłe w porównaniu z resztą.???
oblicz log₇50=log₇2*5²=log₇2+log₇5²=log₇2+2log₇5= a/(1-a)+

b) log₃20=a
log₃2²+log₃5=a→→ 2 log₃2+b -1=a→→log₃2=(a-b+1)/2
log₃15=b
log₃3+log₃5=b
log₃5=b -1
log₃5=log₂5/log₂3=b -1→log₂5=(b -1)*log₂3=2(b -1)/(a-b+1)
oblicz log₂360=log₂(3*2*2*3*2*5)=2log₂3+3log₂2+log₂5=
4/(a-b+1) +3 +2(b -1)/(a-b+1)=(4+3a-3b+3+2b-2)/(a-b+1)=
(3a-b+5)/(a-b+1)

log₂360=(3a-b+5)/(a-b+1)

c) log ₅4=a → log ₅2²=a →2 log ₅2=a → log ₅2=a /2
log₅27=b → log₅3³=b →3 log₅3=b →log₅3=b/3
oblicz log₅6= log₅2+log₅3= a /2 +b/3

log₅6= a /2 +b/3 lub (3a+2b)/6